Metabolism of NK cells during viral infections - Osuna-Espinoza, Kenia Y.; Rosas-Taraco, Adrián G. (Frontiers in Immunology, 2023)
Cellular metabolism is essential for the correct function of immune system cells, including Natural Killer cells (NK). These cells depend on energy to carry out their effector functions, especially in the early stages of viral infection. NK cells participate in the innate immune response against viruses and tumors. Their main functions are cytotoxicity and cytokine production. Metabolic changes can impact intracellular signals, molecule production, secretion, and cell activation which is essential as the first line of immune defense. Metabolic variations in different immune cells in response to a tumor or pathogen infection have been described; however, little is known about NK cell metabolism in the context of viral infection. This review summarizes the activation-specific metabolic changes in NK cells, the immunometabolism of NK cells during early, late, and chronic antiviral responses, and the metabolic alterations in NK cells in SARS-CoV2 infection. The modulation points of these metabolic routes are also discussed to explore potential new immunotherapies against viral infections.